Harnessing beta-cell replication: advancing molecular insights to regenerative therapies in diabetes - Vasavada, Rupangi C.; Dhawan, Sangeeta (Frontiers in Endocrinology, 2025)
Diminished functional beta-cell mass is a key pathogenic mechanism underlying both type 1 and type 2 diabetes (T1D and T2D), precipitated by the progressive impairment of insulin secretion, loss of cellular identity, and ultimately, beta-cell death. The replenishment of beta-cell deficit through the transplantation of pancreatic islets from cadaveric donors or beta-cells derived from human embryonic stem cells has shown transformative therapeutic potential. However, the regeneration of functional beta-cell mass in vivo remains an important therapeutic goal, as a more physiological and scalable approach. Effective beta-cell replenishment must address the underlying causes of beta-cell loss, such as cellular stress and autoimmunity, while simultaneously promoting beta-cell regeneration, function, and survival. Advances in the mechanistic underpinnings of beta-cell differentiation, growth, and survival, coupled with cutting-edge high-throughput screening methods have accelerated the discovery of novel therapeutic targets and small-molecule interventions. Current strategies for in vivo beta-cell expansion include modulating the cell-cycle to promote replication, reprogramming non-beta-cell lineages into beta-cells, and enhancing beta-cell survival. However, the limited regenerative capacity and inherently high stress sensitivity of beta-cells pose significant barriers to their in vivo expansion, further complicated by the fundamental conflict between replication and functional maintenance, and the high vulnerability of replicating cells in a metabolically stressed environment. There has been tremendous progress in developing approaches that simultaneously promote beta-cell expansion and function. In this review, we discuss the recent advances in beta-cell expansion, along with remaining challenges and emerging opportunities to address them.